How Are Policies Promoting Physical Activity Monitored? Results of a Systematic Review - Messing, Sven; Tcymbal, Antonina; Abu-Omar, Karim; Gelius, Peter (Book of Abstracts, 2022)
Objectives While there are numerous efforts to monitor policies that promote health-enhancing behaviours such as physical activity, the monitoring methods used by international organizations and academic institutions differ substantially. This study aims to describe the review methods currently in use and discuss potential benefits and pitfalls of these methods. Methods A systematic search was conducted in five scientific databases, using variations of the terms “physical activity”, “policy” and “monitoring”. Two reviewers independently screened 7,604 and included 121 studies for full text analysis. During full text analysis, information on the methods applied for policy monitoring was extracted. Findings Studies monitoring policies for physical activity promotion at national, regional and local level were identified, as well as studies with a specific focus on the school and childcare setting. A majority of the studies utilized an established tool for policy monitoring, e.g. the EU/WHO Physical Activity Monitoring Framework. Based on the level of government involvement, studies could be broadly classified into research-driven, government-driven or co-production approaches. Discussion Each of the approaches in use to monitor policies for physical activity promotion has certain strengths and weaknesses. A careful reflection on the different approaches is needed, as it has implications for data quality, capacity building, and potential policy impact. A question of particular importance is whether (and if so, to what extent) governments should be involved in policy monitoring. Conclusion Raising awareness for the importance of choosing appropriate policy monitoring methods will enable decision-makers and researchers make informed choices for future monitoring effort